Grassland biomass dynamics along an altitudinal gradient in the Pampa - Pérez, Carolina Alejandra (2000)
Above and below-ground biomass and necromass dynamics were assessed for 3 grassland sites located at 550, 850, and 1,025 m elevation in Sierra de la Ventana range (38 degrees 1'S 62 degrees 2'W) in Argentina. The objective was to determine if differences existed in dry matter structure, mycorrhizae infection, net primary productivity (NPP) partitioning to aboveground and belowground tissues, senescence and litter fall, and seasonal patterns of dry matter fluxes with altitude. Soil properties, water budgets and temperature at the sites were also assessed. Biomass plus necromass (without litter) was 1,184 +/- 41, 1,208 +/- 70, and 1,507 +/- 63 gDM m-2 for the lower, intermediate and upper sites, respectively. The below:aboveground biomass ratio increased with elevation. Total NPP was 1,131, 1,280, and 1,157 gDM m-2 year-1, respectively, for the 3 grassland sites. belowground allocation of net productivity increased with altitude. Both mass and proportion of thin roots increased with elevation, and so did mycorrhizae infection. The aboveground and belowground turnover rates decreased with altitude, but rates were faster for aboveground tissues. We found different temporal patterns in productivity, senescence and disappearance among grassland sites despite similar total NPP. Water holding capacity of soils and temperature were important factors related to several of the observed trends in structure and function. Differences in grassland structure and fluxes are discussed as related to soils and local climate at each site.